Tick-borne Rickettsia, Anaplasma, Theileria, and enzootic nasal tumor virus in ruminant, PET, and poultry animals in Pakistan - Jamil, Anjum; Yu, Ze; Wang, Yuxin; Xin, Qing; Gao, Shan; Abdul Wahab, Muhammad; Han, Xiaohu; Chen, Zeliang (Frontiers in Microbiology, 2024)
Tick-borne diseases (TBDs) have a large impact on animal health status and the livelihood of livestock owners, particularly in developing countries. Although climatic and ecological conditions in Pakistan may favor the transmission of tick -borne pathogens (TBPs), only a few systematic studies have been carried out on TBPs and the diseases that they cause in this country.To improve our understanding of the distribution of TBPs, 213 ticks were collected from ruminants and Pet animals. After molecular and phylogenetic analysis identification, ticks were pooled into different pools (Hyalomma anatolicum =80, Rhipicephalus microplus =35, Hyalomma scupense =23, Rhipicephalus turanicus =70 and Rhipicephalus sanguineus=5 ) based on their species, locality of collection and the host. DNA from each pool was screened by a PCR amplification for the presence of Theileria , Rickettsia , Anaplasma , and Enzootic Nasal tumor Virus(ENTV) . The detected pathogens not only included species that were known to be endemic in Pakistan, such as, 11 (5.16%) for Anaplasma, 1 (0.47%) for Rickettsia , and 9 (4.23%)for Theileria . but also several TBPs that had not been reported to occur in Pakistan before, 3(1.41%) were positive for Enzootic Nasal Tumor Virus(ENTV) . Phylogenetic analysis of the whole genome sequence of the Pakistani Enzootic Nasal Tumor Virus(ENTV) strain confirmed its similarity with the Chinese strain, while Anaplasma has similarity with Pakistan and Saudi Arabia, Rickettsia with Pakistan and Spain, and Theileria with Pakistan, China, Japan, and Spain.The pathogenicity of these novel species remains to be examined. This study reveals that there is a considerably wider range of TBPs in Pakistan, including various zoonotic infections, than was previously thought.. This information advances TBP epidemiology and will contribute to improve future control measures.